World and Domestic Experience in the Construction of Sidewalks - A., Zokirova L.; A., Xatamova P. (European Journal of Life Safety and Stability (2660-9630), 2022)
This article examines and analyzes foreign and domestic experience, achievements and shortcomings in the formation of sidewalks. Suggestions for landscaping of sidewalks are included.